Metabolic syndrome – a risk factor for all-cause disability pension: a prospective study based on the Swedish WOLF cohort - Lidén, Edvard; Karlsson, Berndt; Torén, Kjell; Andersson, Eva (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVE ': 'The aim was to study the impact of metabolic syndrome on the risk for disability pension among Swedish employees. ' ' METHODS ': 'A working population-based prospective cohort [Work, Lipids and Fibrinogen (WOLF) cohort, N=10 803], was linked to national registry records of all-cause disability pension for the period 1992–2013. Occupational health service data included 1992–2009 anthropometric measurements, blood samples, and questionnaires. Metabolic syndrome was defined according to International Diabetes Federation criteria, and risk for any all-cause disability pension was analyzed using Cox proportional hazard regression as hazard ratios (HR) with 95% confidence intervals (CI) adjusted for age, sex and other covariates. ' ' RESULTS ': 'Of the employees, 17.9% (men 21.5%, women 9.7%) met the criteria for metabolic syndrome. The prevalence of all-cause disability pension was 15.2% in men with metabolic syndrome and 7.5% in men without metabolic syndrome; for women, the corresponding results were 23.2% and 12.7%. After adjustment for socio-demographic factors, health behaviors, work-related factors, diabetes, and obesity, the risk for all-cause disability pension among subjects with metabolic syndrome displayed an HR of 1.37 (95% CI 1.18–1.60). Results were similar for men and women. In a subgroup, further adjustment for chronic diseases resulted in an HR of 1.32 (95% CI 1.04–1.68). ' ' CONCLUSION ': 'This study demonstrates an increased risk for all-cause disability pension, even after adjustment for other risk factors, among Swedish employees with metabolic syndrome compared to those without at baseline.
Keywords: abdominal obesity; blood lipid; disability; disability pension; employee; glucose; hypertension; longitudinal; metabolic syndrome; prospective study; Sweden; WOLF cohort; work ability